2017
DOI: 10.1016/j.jhydrol.2016.12.040
|View full text |Cite
|
Sign up to set email alerts
|

A global review on hydrological responses to forest change across multiple spatial scales: Importance of scale, climate, forest type and hydrological regime

Abstract: Despite extensive studies on hydrological responses to forest cover change in small watersheds, the hydrological responses to forest change and associated mechanisms across multiple spatial scales have not been fully understood. This review thus examined about 312 watersheds worldwide to provide a generalized framework to evaluate hydrological responses to forest cover change and to identify the contribution of spatial scale, climate, forest type and hydrological regime in determining the intensity of forest c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
259
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 341 publications
(289 citation statements)
references
References 218 publications
(185 reference statements)
23
259
0
7
Order By: Relevance
“…precipitation recycling). Both views are supported by observational and modelling studies (Ellison et al, 2012;Zhang et al, 2016). For instance, previous studies have reported that forest cover reduction in large basins can result in both increased (Wei and Zhang, 2010) or decreased (Coe et al, 2009) mean river flows.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…precipitation recycling). Both views are supported by observational and modelling studies (Ellison et al, 2012;Zhang et al, 2016). For instance, previous studies have reported that forest cover reduction in large basins can result in both increased (Wei and Zhang, 2010) or decreased (Coe et al, 2009) mean river flows.…”
Section: Introductionmentioning
confidence: 67%
“…variations in the water balance partitioning) to forest cover change is to exclude the effect of non-forest drivers on runoff (Renner et al, 2014). This can be even more challenging 25 for large basins with various confounding factors including artificial reservoirs and associated water resources schemes (Zhang et al, 2016). Although more-detailed studies are essential to understand water balance partitioning dynamics in different basins, as well as to characterize the influence of forest and non-forest drivers, our observation-based analysis allows to infer that variations in water balance partitioning patterns are related to variations in forest cover.…”
mentioning
confidence: 99%
“…Moreover, hydrological responses are compounded by the spatially diverse effects of climate, vegetation, soil, and topography (Li et al, 2017;Zhang et al, 2017). For example, several hydrological models have been applied to test the effect of the spatial distribution of a hydrological variable (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mean and extreme river flows are global-change-sensitive components of river flow regimes that are determinant for many 10 ecological and societal processes (Sterling et al, 2013;Piao et al, 2007;Coe et al, 2009;Mahe et al, 2005;Lima et al, 2014;Zhang et al, 2016). Landscape and climate alterations foreshadow shifts of precipitation and river flow regimes (Botter et al, 2013;Boers et al, 2017;Hirota et al, 2011;Davidson et al, 2012;Khanna et al, 2017;Lawrence and Vandecar, 2015;Zemp et al, 2017;Sampaio et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This is a key reason why findings from small river basins about the hydrological effects of forest loss (e.g. from paired catchment studies) cannot be extrapolated to large river basins (Zhang et al, 2016;Ellison et al, 2012;Zhou et al, 2015).…”
mentioning
confidence: 99%